Teacher’s Perspective in Teaching Reading Comprehension Using Reciprocal Strategy - Leny Dwi Puspita; Ermawati Zulikhatin Nuroh (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
The Indonesian government has determined that English is a compulsory subject in junior high schools, senior high schools, and universities. English in junior high school includes four mandatory skills: listening, reading, speaking, and writing. In the teaching process, teachers are expected to be perfect. The teacher must be "perfect"; it means they have to be active, creative, innovative, interesting, and achievers so that students can focus on the lessons in class. However, most students have difficulty learning English, especially reading or understanding texts. This research was conducted with the aim of describing the Teacher's Perspective in Teaching Reading Comprehension Using a Reciprocal Strategy. This research was conducted at SMPN 1 Jabon using qualitative methods, data obtained from interviews and observations. The subject in this study is an English teacher at SMPN 1 Jabon. The results of this study indicate that mastery of good learning strategies is an important component of education in supporting the professional duties of teachers as educators. Teachers use reciprocal teaching as a strategy in their learning. Reciprocal strategies can improve students' reading comprehension because students know the essence of what they read globally. In addition, the teacher can also assist students in understanding the meaning contained in the reading text material that has been explained during the reading class.